2020
DOI: 10.1007/s10741-020-10041-1
|View full text |Cite
|
Sign up to set email alerts
|

Sodium glucose cotransporter 2 inhibitors: mechanisms of action in heart failure

Abstract: Diabetes is a key independent risk factor in the development of heart failure (HF) and a strong, adverse prognostic factor in HF patients. HF remains the primary cause of hospitalisation for diabetics and, as previous studies have shown, when HF occurs in these patients, intensive glycaemic control does not directly improve the prognosis. Recent clinical studies assessing a new class of antidiabetic drugs, sodium-glucose cotransporter 2 inhibitors (SGLT2is) showed some unexpected beneficial results. Patients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 110 publications
(263 reference statements)
2
23
0
4
Order By: Relevance
“…Activating Caspase-1 can induce the release of the level of IL-1β and IL-18. IL-18 can promote the production of TNF-α, while TNF-α reacts to Caspase-1, thus forming an inflammation reaction waterfall, promoting cell death, and eventually leading to HF (Mieczysław et al, 2020). In the present study, we also demonstrated that SYDC could inhibit apoptosis by downregulating the mRNA expressions of Bax, Caspase-3, and Caspase-1 and upregulating the mRNA expressions of Bcl-2 in the verapamil-treated larval zebrafish model.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Activating Caspase-1 can induce the release of the level of IL-1β and IL-18. IL-18 can promote the production of TNF-α, while TNF-α reacts to Caspase-1, thus forming an inflammation reaction waterfall, promoting cell death, and eventually leading to HF (Mieczysław et al, 2020). In the present study, we also demonstrated that SYDC could inhibit apoptosis by downregulating the mRNA expressions of Bax, Caspase-3, and Caspase-1 and upregulating the mRNA expressions of Bcl-2 in the verapamil-treated larval zebrafish model.…”
Section: Discussionsupporting
confidence: 67%
“…ROS-mediated nuclear factor-kappa B (NF-κB) signaling pathway is an emerging inflammatory and apoptosis signaling pathway (Sahar et al, 2020). Accumulation of ROS leads to the activation of NF-κB, which is the basic transcription factor that activates inflammation (Mieczysław et al, 2020). Prolonged activation of NF-κB causes the release of both a large number of proinflammatory cytokines and an intensification of cardiomyocyte apoptosis (Mieczysław et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…During this lack of oxygen, ketone bodies can be better substrates than FAs at producing ATP due to a more favorable P/O ratio (2.50). Ketone bodies are also better than glucose, even though their P/O values are not significantly different [ 155 , 208 , 209 ]. β-HB must be converted into acetoacetate to generate energy.…”
Section: Metabolic Reprogramming By Sglt2-ismentioning
confidence: 99%
“…Die zugrunde liegenden Mechanismen der kardialen und renalen Protektion von SGLT2-Hemmern sind Gegenstand umfangreicher Studien [138][139][140][141][142].…”
Section: Empagliflozinunclassified